Analyzing the stock markets role as a source of capital formation in Pakistan - Hakim Ali Kanasro; Mumtaz Ali Junejo; Mansoor Ahmed Junejo (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2011)
This paper is to examine the stock markets role in the capital formation in Pakistan from the period 1st January 2001 to 31st December 2008. This analytical study is based on the data collected from the secondary sources such as State Bank of Pakistan and three stock exchanges; Karachi, Lahore and Islamabad Stock exchanges. The stock market size of capital, number of listed companies and liquidity positions has been examined in the study. The study reveals that Karachi Stock exchange is the oldest and biggest Stock exchange of Pakistan and it is the first mover to adapt institutional developments, new policies and procedures in the business of securities exchange and shares a big role in the capital formation in Pakistan. In recent years all stock exchanges have implemented the advanced technology and fully automated trading systems. This has changed the stock markets role in the capital formation as great boom has been observed during the study period.
Keywords: 330; Stock Exchange; Investment; Capitalization; Economic growth; Financial Institutions; Aktienmarkt; Wirkungsanalyse; Investition; Wirtschaftswachstum; Pakistan